The distribution of lignin and xylan in the inner and surface layers of the fiber from eucalyptus kraft pulp and its effects on oxygen delignification - Bacarin, Giovani Boaventura [UNESP]; Cabrera, Flávio Camargo [UNESP]; Da Silva, Marcelo Rodrigues; Job, Aldo Eloizo [UNESP] (FapUNIFESP (SciELO), 2017)
The chemical structure and composition of lignin and hemicellulose, as well as the distribution between inner and outer layers of fiber, can adversely affect bleaching operations or fiber-fiber bond on pulp and, consequently the papermaking process. Herein, we have implemented the fractionation and mechanical peeling techniques in order to identify the fines composition from eucalyptus cellulose as well as to verify the effect over xylan and lignin contents and the impact on oxygen delignification. Lignin and xylans in the material removed from the fiber surface (fines) were measured around to 7.6% and 12% of the composition, respectively. The lignin value is three times higher than the percentage measured to original fiber composition (without treatment). The residual xylans content on the pulp, after treatment of fines removal and peeling, was slightly reduced, around 3% for both treatments as well as fractionation and peeling methods decrease the oxygen delignification efficiency.
Keywords: Fiber surface; Fractionation; Lignin; Mechanical peeling; Oxygen delignification; Xylans